(3OhQ GdbGfhf GdLfGFj aj ecGaMI GdaSGO GdSjGSj (B/s - (3GdeQGZj, CMeO YHO GddGgs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3JXgQ CgejI gPG GdcJGH aj JMhd GdaSGO ef XGgQI Edi fXGe hWQjbI ddMjGI aj cKjQ ef GdOhd GdfGejI hcGf ef GdWHjYj Cf jchf dGfJTGQ gPG GdSdhc GdaGSO hGdeOeQ BKGQ hJOGYjGJ SdHjI Ydi eLed GdChVGY GdGbJUGOjI hGdGLJeGYjI hGdSjGSjI hGdKbGajI aj GdOhd GdfGejI hYdi VhA Pdc LGA gPG GdcJGH eJfGhdG (B((3eGgjI GdaSGO GdSjGSj hGdehGLgI GdLfGFjI ddaSGO GdSjGSj hGdSjGSI GdLfGFjI decGaMI XGgQI GdaSGO GdSjGSj(B)s
(3edGMb (B: (3UaMI (B293.s
(3HHdjhLQGajI (B: (3UaMI (B253-292.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdaSGO GdSjGSjs -- (3hbGjIs -- (3bhGfjf hJTQjYGJs; (3GdaSGO GdEOGQj s; (3GdaSGO GdeGdjs; (3GdaSGO GdJTQjYj s; (3EaSGO GdMces; (3GdMjGI GdSjGSjIs; (3LQGFe GdaSGOs